2021
DOI: 10.3390/ijerph18136954
|View full text |Cite
|
Sign up to set email alerts
|

Toilet Paper, Minced Meat and Diabetes Medicines: Australian Panic Buying Induced by COVID-19

Abstract: The COVID-19 pandemic has impacted the management of non-communicable diseases in health systems around the world. This study aimed to understand the impact of COVID-19 on diabetes medicines dispensed in Australia. Publicly available data from Australia’s government subsidised medicines program (Pharmaceutical Benefits Scheme), detailing prescriptions by month dispensed to patients, drug item code and patient category, was obtained from January 2016 to November 2020. This study focused on medicines used in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…During the pandemic and compared to the previous year, the proportion of patients with medications increased in our study and for SGLT-2 and GLP-1 a significant effect was attributable to the pandemic. Other studies observed: an increase in insulin [ 39 ] and both insulin and OAD medications [ 40 , 41 ], during the first month of pandemic as compared to the year before; a decrease in OAD during the first four months of the pandemic [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic and compared to the previous year, the proportion of patients with medications increased in our study and for SGLT-2 and GLP-1 a significant effect was attributable to the pandemic. Other studies observed: an increase in insulin [ 39 ] and both insulin and OAD medications [ 40 , 41 ], during the first month of pandemic as compared to the year before; a decrease in OAD during the first four months of the pandemic [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet we observed that the trend of increasing utilization slowed in July for antihyperglycemic medication orders and ED visits, and for HbA 1c tests and outpatient visits, rates started to decline. This could potentially be explained by increased national infection rates starting in mid-July, with cases doubling in 19 US states (27), news that may have influenced local care-seeking behaviors. Thus, individuals with diabetes experienced disruptions in care during multiple phases of the COVID-19 pandemic, including periods of strict mitigation policies and periods of elevated infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…The more gradual decline in medication orders in cities may be driven by the peak in medication order rates that occurred in townships and boroughs, but not cities, immediately before the pandemic. The peak in medication orders early in the pandemic has been previously attributed to “panic buying” because of concerns about possible medication shortages ( 28 ). Individuals residing in townships and boroughs may have more proactively prepared for a potential disruption in medication supplies, obtaining medications in early March 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the growth in high-quality, real-world evidence addressing emergent clinical questions about vaccines and medicines across the globe [67][68][69], Australia has been silent on these issues. While some Australian population-based studies are emerging around the changes in prescribed medicine use during the pandemic [70][71][72][73][74][75], none address questions of significant public interest regarding the effectiveness and safety of therapies for COVID-19. This issue has become even more pressing with the emergence of the SARS-CoV-2 Delta and Omicron variants.…”
Section: Characteristics Of Australian Pharmacoepidemiological Research Studiesmentioning
confidence: 99%